Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009 International Conference on Advanced Computer Control 2009
DOI: 10.1109/icacc.2009.149
|View full text |Cite
|
Sign up to set email alerts
|

Vehicle Detection and Counting by Using Real Time Traffic Flux through Differential Technique and Performance Evaluation

Abstract: This paper is dedicated to detecting and counting vehicles in day environment by using real time traffic flux through differential techniques. The basic idea used is variation in the traffic flux density due to presence of vehicle in the scene. In the present work a simple differential algorithm is designed and tested with vehicle detection and counting application. Traffic flux estimation will play vital role in implementing vehicle detection and counting scheme. Real time dynamic scene analysis has become ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 7 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…There are a number of studies for estimating vehicle flow via vehicle detection and tracking. Common methods first subtract the background image, segment the vehicles in the image, and use a combination of features to track the vehicles [1,7,16,17]. These studies have shown high accuracy (90% to 96%) and can be implemented in real-time; however, the tracking algorithms such as Kalman filtering or distance of features have substantial difficulties with large object displacements common in low frame-rate cameras.…”
Section: Related Workmentioning
confidence: 99%
“…There are a number of studies for estimating vehicle flow via vehicle detection and tracking. Common methods first subtract the background image, segment the vehicles in the image, and use a combination of features to track the vehicles [1,7,16,17]. These studies have shown high accuracy (90% to 96%) and can be implemented in real-time; however, the tracking algorithms such as Kalman filtering or distance of features have substantial difficulties with large object displacements common in low frame-rate cameras.…”
Section: Related Workmentioning
confidence: 99%
“…Pornpanomchai et al [5] studied video vision for vehicle counting. Mohana et al [6] studied the counting of vehicles in real-time. Zhao and Wang [7] studied vehicle counting in mixed traffic zones.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies deal with the determination of the number of vehicles in real-time traffic flux. Traffic intensity is estimated due to the presence of a vehicle in the sequence [4,5].…”
Section: Introductionmentioning
confidence: 99%